(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article highlights the basics of the scientific and practical model of electronic government in the digital economy and provides information about them. The digital economy has a long list of unique features that cannot be found in other types of economies. Free goods and services like Wikipedia, email services like Gmail, and digital maps like Google Maps are all components of the modern digital economy with enormous economic values.